P112 Association of intussusception and celiac disease in children: a case report and literature rewiew. (June 2019) - Mainetti, Martina; Graziani, Vanna; Radice, Caterina; Marchetti, Federico
Abstract : We present the case of a 22-month-old child, with an acute onset of celiac disease (CD) and recurrents intestinal intussusception. The child had a marked loss of appetite for 1 month and episodes of food vomiting, almost at every meal, at a distance of about 2 hours, sometimes associated with short-term crying. An abdominal ultrasound has documented a picture compatible with intestinal intussusception (INI), which spontaneously resolved during the ultrasound examination. Since the criteria of the ESPGHAN guidelines were not met in order to be able to diagnose celiac disease without biopsy (in particular there were no TTG IgA values> 10 times the norm), esophageal-gastro-duodenoscopy was performed. Histological examination confirmed CD. The child was placed on a gluten-free diet with rapid improvement of the clinical conditions and gradual recovery of appetite. At home wellness in the first days with subsequent appearance of episodes of crying at night, lasting about 5–10 minutes, all at spontaneous resolution. To progressively increase the episodes of crying it was decided to perform again an ultrasound of the abdomen with evidence of a image compatible again with a picture of INI. Subsequent ultrasound evaluations, performed in the following days, showed the spontaneous resolution of the described picture. In view of the clinical picture, characterized by recurrent INI, it was decided to resume steroid therapy (budesonide, 3 mg/day), waiting for a response to the gluten-free diet. After 2 weeks of complete well-being with clear improvement of the clinical condition, steroid therapy was gradually discontinued, with no more episodes of possible intermittent intestinal intussusception. The prevalence values of intestinal infection in CD are equal to 1.6% in adults and ranging from 0.037% to 1.2% in children, in different studies. In a cohort study, a prevalence of about 1% of INI was detected in children with a new diagnosis of MC, before starting the gluten diet. Given that not all children with CD and abdominal pain have undergone abdominal imaging, this estimate refers to clinically significant cases. The pathogenetic mechanism is not yet fully understood. The course of INI to the diagnosis of CD is generally benign, with spontaneous resolution of the picture with a gluten-free diet. In recurrent intussusception it is important to consider the treatment with steroids before resorting to a more invasive approach, which should be reserved for cases with symptoms of intestinal obstruction.